Research progress of nursing interventions for catheter-associated urinary tract infection (导管相关性尿路感染护理干预的研究进展) - DU Yemeng (杜叶萌); LI Yanli (李彦丽); ZHANG Lihua (张丽华) (中西医结合护理)
The use of catheters is very common in clinical care and is a highly invasive procedure, and catheter-associated urinary tract infection (CAUTI) is an important cause of hospital-acquired infections. CAUTI is a serious complication caused by catheter insertion, usually within 48 hours of catheterization or after removal of the catheter. This article reviews the nursing measures for the prevention of CAUTI in perspectives of influencing factors, selection of catheter, catheter placement and catheter maintenance, aiming to promote the development of long-term indwelling catheter technology and provide reference for prevention and treatment of CAUTI in clinical practice. (导管相关性尿路感染(CAUTI)是医院内感染最常见的类型之一。CAUTI是一种由插入尿管引起的严重的并发症, 通常出现在患者接受插管治疗后的48 h内或者在取出导尿管之后。本本研究就引发CAUTI的主要影响因素、导尿管的选取、导管的留置操作、管路维护以及医院管理等方面进行综述, 旨在为防治CAUTI提供可靠参考。)